Implicit social cognition mediator for the development of Malaysian Career Factor Inventory (MYCFI) - Md Yasin, Ina; Adam Assim, Mohamad Ibrani Shahrimin (University Publications, 2013)
Current and existing Career Factor Inventory (CFI) lacks the depth in sociocultural parameters and social psychological ‘imaginations’. Implicit social cognition may offer some pertinent viable understandings in career indecision, which has been one of the central research issues of counselling and psychology, especially in young adults who are in the midst of making critical life decisions. According to Schneider (1991; Bazerman & Tenbrussel, 1998), social cognition has become the dominant perspective in psychology. However, it is important to understand that the ‘dark matter; of the mind involves the implicit processes (Schacter, 1987; Amodio & Ratner, 2011). Malaysia’s economy had been growing enormously by investing heavily in education and technology. The Malaysia success has had a tremendous sociological impact that is rarely mentioned but highly meaningful to all Malaysians. This is indeed the driving force behind the career-mindedness of most young Malaysians whose career choice-making is often fraught with numerous challenges. Therefore, this study is premised in an effort to discover the career indecision’s phenomena among the potential graduates and students from the Institution of Higher Learning in Malaysia through the development of Malaysian Career Factor Inventory (My-CFI) with denomination of social psychological’ lenses as eigenvector mediators. It is argued that behaviour or at least some of the mediators can be influenced by implicit social cognition. Theory of Planned Behaviour is used as the underpinning theory, which is hypothesised to be understood and it should be viewed together with the Theory of Cognitive Dissonance. It is meant to give the fundamental understandings that acknowledge both social cognition and planned behaviour approaches. The predictability of the precision measurement of extrapolating intention before one commits to any behaviour is also discussed. Preliminary results are presented and analysed.